Enhancing Islamic Education Student’s Reading Comprehension by Using Authentic Material - Sulaiman Sulaiman (AT-TURATS, 2020)
Abstract The study is aimed to enhance reading comprehension of the second semester students of PAI students of FTIK IAIN Pontianak by using Authentic Material. This is an action research with the subjects were 34 students of Islamic education students (PAI)FTIK IAIN Pontianak in academic year 2018/2019. This is in two cycles and the result was it is effective in enhancing the Islamic education students’ reading comprehension. These materials were much effective when the students together with the authentic task. The improvements such as more focus and active in participating classroom activities in classroom, also motivated and interesting in reading activities. And the class atmosphere is more enjoy and enthusiastic